EFEKTIVITAS SISTEM INFORMASI PARTAI POLITIK (SIPOL) DALAM PROSES PENDAFTARAN CALON PESERTA PEMILU TAHUN 2024 BERDASARKAN PUTUSAN BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) NOMOR: 003/PS.REG/BAWASLU/X/2022 - Wisnu Nugraha (LPPM Universitas Ekasakti Padang, 2023)
This writing is meant to figure out how effective using Sipol is in the registration process for Candidates for the 2024 Election. The method used in this research is the library research method using laws and regulations and Bawaslu decisions as data material for research. The problems to be discussed in this study are (1). What are the obstacles in implementing Sipol in the registration process for Candidates for Election Contestants?, and (2). How effective is using Sipol based on Bawaslu Decision Number: 003/PS?REG/BAWASLU/X/2022? The results of this study are in the form of conclusions, namely (1). Obstacles in the implementation and use of Sipol come from HR factors, both HR from Political Parties as users of Sipol, factors from weak Sipol servers which often experience errors so they cannot be used optimally, as well as elements from the limited time in the process of using Sipol, namely at the stage of the verification process political party data, (2). The maximum effectiveness of the use of Sipol has not been achieved, it can be seen based on the Bawaslu Decision Number: 003/PS.REG/BAWASLU/X/2022, where the Republican Party was declared disqualified as a Candidate for the 2024 Election based on the KPU Decree which was caused by obstacles to the use of the Sipol application , The Bawaslu Adjudication Committee stated that technical problems in using Sipol should not occur because it is contrary to the principles of election administration including the principles of independence, honesty, fairness, legal certainty, orderly, openness, proportionate, professional, accountable, effective and efficient.